2010
DOI: 10.1186/1472-6750-10-62
|View full text |Cite
|
Sign up to set email alerts
|

Engineering of N. benthamiana L. plants for production of N-acetylgalactosamine-glycosylated proteins - towards development of a plant-based platform for production of protein therapeutics with mucin type O-glycosylation

Abstract: BackgroundMucin type O-glycosylation is one of the most common types of post-translational modifications that impacts stability and biological functions of many mammalian proteins. A large family of UDP-GalNAc polypeptide:N-acetyl-α-galactosaminyltransferases (GalNAc-Ts) catalyzes the first step of mucin type O-glycosylation by transferring GalNAc to serine and/or threonine residues of acceptor polypeptides. Plants do not have the enzyme machinery to perform this process, thus restricting their use as bioreact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
46
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 63 publications
2
46
1
Order By: Relevance
“…The results are essentially in complete disagreement with those reported by Daskalova et al (23), which highlights the need for structural verification of products produced with glycoengineering. We used transient expression of enzymes and reporter substrates to identify requirements for establishing efficient glycosylation of mammalian O-glycoproteins (see Fig.…”
contrasting
confidence: 57%
See 1 more Smart Citation
“…The results are essentially in complete disagreement with those reported by Daskalova et al (23), which highlights the need for structural verification of products produced with glycoengineering. We used transient expression of enzymes and reporter substrates to identify requirements for establishing efficient glycosylation of mammalian O-glycoproteins (see Fig.…”
contrasting
confidence: 57%
“…Thus, the original proposal of the presence of sialic acids in plant glycoproteins (25,26) was later shown likely to be due to contaminants (27). Furthermore, Daskalova and co-workers (28) more recently reported that the VVA lectin recognizes noncarbohydrate epitopes by Western blotting in plants, thus casting serious doubts on the conclusions drawn in their previous publication (23).…”
mentioning
confidence: 91%
“…Here, we have established O-glycosylation capacity stably in two different plant cell systems: (1) tobacco BY-2 suspension cells, which offers potential for the secretion of products (Hellwig et al, 2004) and has low reproductive constraints with regard to the propagation and manipulation of transgenic lines; and (2) soil-grown Arabidopsis, which has a comprehensive transferred DNA knockout repertoire (http:// signal.salk.edu/) enabling, for example, the manipulation of endogenous-derived PTMs. A previous report proposed that a three-component machinery (additionally including a UDP-GalNAc-T) was required for the introduction of O-glycosylation in plants (Daskalova et al, 2010), but our results using transient (Yang et al, 2012) and now also stable introduction of O-glycosylation machineries clearly demonstrate that the UDP-GalNAc-T is not required.…”
Section: Discussionmentioning
confidence: 37%
“…The restricted occurrence or sequence specificity of these plant-specific types of O-glycosylation should make plants an ideal candidate cell system for the custom design and buildup of O-glycosylation from scratch with respect to both sites of O-glycan attachment and O-glycan structures. Daskalova et al (2010) initially started engineering plants for mammalian O-glycosylation and suggested that GalNAc O-glycosylation in Nicotiana benthamiana plants required a Glc(NAc) C4-epimerase, a UDP-Gal (NAc) transporter, and a human GalNAc-T. We subsequently tested a variety of design strategies for the introduction of GalNAc O-glycosylation in plants using transient expression of the glycogenes in N. benthamiana and found that O-glycosylation capacity was achieved by the introduction of only the Pseudomonas aeruginosa Glc(NAc) C4-epimerase (WbpP; Creuzenet et al, 2000) and a human GalNAc-T. The apparent discrepancy with regard to the requirement for the introduction of a UDP-GalNAc transporter is not fully clarified, but the study by Daskalova et al (2010) was solely based on lectin labeling, and the authors subsequently demonstrated that the lectins used detect endogenous plant proteins (Reaves et al, 2011), causing serious concerns with regard to the original findings.…”
mentioning
confidence: 99%
“…Also, N-glycosylation differences could represent a severe limitation on the use of plant-made pharmaceuticals that triggered abundant work on the fi eld (Bardor et al 2006 ), O-glycosylation, which has been less studied (Daskalova et al 2010 ).…”
Section: Plant Glycosylationmentioning
confidence: 99%